2015
DOI: 10.1097/inf.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Successful Early Infant Diagnosis of HIV Infection at Primary Care Level in Malawi

Abstract: HIV-infected women seeking early infant HIV diagnosis (EID) services in Malawi were asked about factors potentially associated with returning for EID results. Many (33.3%) infants failed to complete the EID process because of time and costs required for multiple visits. Infants of mothers receiving antiretroviral treatment were less likely to drop out (adjusted risk ratio 0.51), suggesting that EID completion may improve in programs providing antiretroviral treatment to all pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…In line with previous studies, we showed that children born to women who received ART are less likely to be lost to follow-up and more likely to be tested for HIV [1518]. Efforts to increase retention and HIV testing could improve the diagnosis of HIV-infected children and their access to ART.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with previous studies, we showed that children born to women who received ART are less likely to be lost to follow-up and more likely to be tested for HIV [1518]. Efforts to increase retention and HIV testing could improve the diagnosis of HIV-infected children and their access to ART.…”
Section: Discussionsupporting
confidence: 88%
“…Neither of the two studies adjusted for missing data in children who were lost to follow-up. As children at higher risk of mother-to-child transmission are underrepresented in routine PMTCT programmes, both studies will have underestimated the risk of mother-to-child-transmission in the Option B+ programme [1518]. The present analysis shows that the degree of underestimation can be substantial.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[14] Recommendations indicate that if an appointment is scheduled with a woman to receive test results (step 4), it either needs to be kept or the woman needs to be contacted to reschedule the appointment. One study found that HIV-infected mothers enrolled in HIV care were less likely to fail to return for their infant's HIV test result (aRR 0.51; 95% CI (0.3 -0.9), [5] therefore providing ART to all pregnant women may lead to a better return. This is encouraging for Malawi, which is implementing lifelong ART for all HIV-positive pregnant women regardless of CD4 count.…”
Section: Discussionmentioning
confidence: 99%
“…The main barriers were expense due to travel time and costs (adjusted risk ratio (aRR) 1.93; 95% confidence interval (CI) 1.1 -3.4), and disclosure by women to their husbands or partners that the infant was being tested (aRR 1.97; 95% CI: 1.0 -3.8). [5] Policy changes in Malawi that support ART initiation for HEI include the Paediatric HIV Care Scale-up Plan (2009 -2013), which authorised all levels of healthcare workers (HCWs) to prescribe ART. However, in practice, paediatric HIV testing, care and treatment were not adequately provided in facilities.…”
mentioning
confidence: 99%